Information Retrieval Design (Book Review) - White, Ryen W. (Journal of the American Society for Information Science and Technology (JASIST), 2006)
Information Retrieval Design is a textbook that aims to foster the intelligent user-centered design of databases for Information Retrieval (IR). The book outlines a comprehensive set of twenty factors, chosen based on prior research and the authors’ experiences, that need to be considered during the design process. The authors provide designers with information on those factors to help optimize decision-making. The book does not cover user needs assessment, implementation of IR databases or retrieval systems, testing or evaluation.